Optimal Design and Analysis of Steering Mechanism of Manned Lunar Rover - Men Shudong; Wang Ping; Zhao Yang; Liu Chunlai (Jixie chuandong, 2015)
In view of the lunar module load limit and lunar complex terrain,the manned lunar mechanism must be light and simple,and has a smaller turning radius,so one type of steering mechanism is designed. The inner and outer wheel turning angles mathematical model is deduced. Based on Ackerman- geometry steering theory,the optimized mathematical model of the steering mechanism is established. By the model optimization and results analysis,the best steering mechanism parameters are obtained. The steering mechanism ADAMS simulation model is established to verify the rationality of the prior analysis,the stress condition of key bars of the steering mechanism is analyzed by using finite element analysis software.